2007
DOI: 10.1089/ast.2006.0124
|View full text |Cite
|
Sign up to set email alerts
|

A Reappraisal of The Habitability of Planets around M Dwarf Stars

Abstract: Stable, hydrogen-burning, M dwarf stars make up about 75% of all stars in the Galaxy. They are extremely long-lived, and because they are much smaller in mass than the Sun (between 0.5 and 0.08 M(Sun)), their temperature and stellar luminosity are low and peaked in the red. We have re-examined what is known at present about the potential for a terrestrial planet forming within, or migrating into, the classic liquid-surface-water habitable zone close to an M dwarf star. Observations of protoplanetary disks sugg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
260
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(264 citation statements)
references
References 186 publications
(241 reference statements)
1
260
0
3
Order By: Relevance
“…They make up approximately 75% of all stars and they have more stable environments over longer time periods than solar-type stars (Tarter et al 2007). They are, therefore, important targets in the search for extrasolar biosignatures (Scalo et al 2007).…”
Section: Photosynthesis On Other Earth-like Planetsmentioning
confidence: 99%
“…They make up approximately 75% of all stars and they have more stable environments over longer time periods than solar-type stars (Tarter et al 2007). They are, therefore, important targets in the search for extrasolar biosignatures (Scalo et al 2007).…”
Section: Photosynthesis On Other Earth-like Planetsmentioning
confidence: 99%
“…The habitability of M-dwarf planets has recently been re-examined by Tarter et al (2007) and Scalo et al (2007). Work reviewed therein contests the conclusions of earlier studies, which found that such planets, which are likely to be tidally-locked to their stars, would be inhospitable to life due either to atmospheric collapse or steep day-night temperature gradients.…”
Section: The Small Star Opportunitymentioning
confidence: 70%
“…In the framework of the adopted models it is found that the maximum life span of super-Earth planets around low mass stars depends almost entirely on the properties of the planet. It is known, however, that other factors are also expected to potentially impact or limit the habitability in the environments of late K and M stars, encompassing effects associated with, e.g., tidal locking of the planet and stellar flares (e.g., Lammer 2007;Tarter et al 2007;Selsis et al 2007;Lammer et al 2009;Segura et al 2010;Heller et al 2011).…”
Section: Habitability Based On the Integrated System Approachmentioning
confidence: 99%